Catch Composition and Seasonal Trend of Mini Purse Seine at Gebang Mekar Fish Landing Site, Cirebon Regency - Didha Andini Putri; Sri Wahyuningsih; Evi Susilawati; Abdul Hadi; Gaga Pradipta (Barakuda 45: Jurnal Ilmu Perikanan dan Kelautan, 2026)
Gebang Mekar Fish Landing Site (PPI) is one of the small pelagic fish landing centers on the northern coast of Cirebon Regency, where the mini purse seine is the dominant fishing gear used by small- to medium-scale fishers. This study aimed to analyze the catch composition of mini purse seine, the environmental factors influencing it, and the production trend of small pelagic fish at PPI Gebang Mekar. The research was conducted from April to June 2025 using a descriptive qualitative method through observation, semi-structured interviews with 20 mini purse seine boat captains (determined using the Slovin formula from a population of 25 captains, 10% margin of error), and secondary production data of PPI Gebang Mekar for 2024 and the first semester of 2025. The results showed that the sampled catch composition was dominated by anchovy (Stolephorus spp.) at 40%, fringescale sardinella (Sardinella fimbriata) at 28%, Indian mackerel (Rastrelliger spp.) at 16%, and scad (Decapterus spp.) at 16%. Secondary data revealed an increasing production trend for anchovy, sardinella, and mackerel from April to June, with year-on-year growth (2024 to 2025) of 4.35%, 7.55%, and 2.78%, respectively. Calm sea currents, low wind speed (±2 knots), and an appropriate east-monsoon fishing strategy were the main factors supporting productivity. This study recommends the sustained integration of primary and secondary data, supported by improved port-level recording mechanisms, to enable more accurate, adaptive management of the mini purse seine fishery oriented toward the sustainability of small pelagic fish resources at PPI Gebang Mekar